Effect of plasma–ozone injection on the performance of a B30 diesel engine under variable load - Alfian Ady Saputra; Muhammad Hardiman Nur Ramadhan; Melati Nurul Insani (Jurnal Polimesin, 2026)
To improve thermal performance and energy conversion efficiency in biodiesel-fueled diesel engines, an active combustion control strategy through modification of the inlet air reactants is crucial. This study investigates the effect of injecting ozone (O₃) produced through a Dielectric Barrier Discharge (DBD) plasma reactor into the air intake of a single-cylinder diesel engine with a variable compression ratio (TV1). Key parameters evaluated included brake power, specific fuel consumption (SFC), air–fuel ratio (AFR), volumetric efficiency, and in-cylinder pressure under varying dynamic loads (1 kg to 9 kg). The experiments were conducted at three compression ratios (14, 16, and 18) with varying ozone doses of 0, 3, 12, 15, and 18 mg. The results showed that the addition of ozone was able to control the combustion duration and phase. The study observed a significant decrease in SFC of up to 25.57% at a compression ratio of 14, an increase in AFR of up to 34.29% at a compression ratio of 16, and an increase in volumetric efficiency of up to 18% at a compression ratio of 18. Cylinder pressure analysis showed an increase in peak pressure and a decrease in net heat release values, indicating a more stable and smoother combustion. These findings confirm that ozone injection acts as an effective chemical cetane improver, especially under operating conditions where the thermal energy of compression is low (compression ratio of 14).